Study Komparatif Efektivitas Strategi Pembelajaran Problem Based Learning (PBL) dengan Discoverylearning (DL) Dalam Pembelajaran IPS Terpadu Siswa Kelas VIISMP N 1 Surakarta Tahun Ajaran 2015/2016 - Bagus Pamungkas, Anandita (2016)
Education is a process to help people develop their potential and thereby able to cope with any changes that occur. Based on this, the teacher should be varied in choosing a strategy by comparing strategies with other strategies. There are so many strategies in teaching them strategies Problem Based Learning (PBL) and Discovery Learning (DL). From both the learning strategies that teachers can compare, Which strategies that fit the material in order to achieve the learning objectives effectively applied in social studies materials and population growth the number of grade VIII SMP N 1 Surakarta. The purpose of this research is to examine and discuss differences in the effectiveness of Problem Based Learning (PBL) with Discovery Learning (DL) on the material number and population growth. The type used in this research is descriptive quantitative research methods to the type of research experiments. The population in this study were students of class VIII SMP N 1 Surakarta academic year 2015/2016. The sample in this research is two experimental class consisting of class VIII G and H. VIII class data collection using experimental techniques, test and documentation. Data were analyzed using test validity, reliability, noermalitas and Wilcoxon tests. Learning outcomes between the two classes of experiments showed the difference. Judging from the results of the average value of the experimental class with the application of learning strategies Problem Based Learning (PBL) in class VIII G, has a value of post test of skills and greater, ie 89.06 dan.3,5 in comparison with the experimental class with the implementation of the strategy learning Discovery learning (DL) at class VIII H, has a value of post test of skills and lower at 83.87 and the difference between the two classes of 3.4 indicates that the strategy of Problem Based learning (PBL) is more effective than the strategy of Discovery learning (DL ).